2000
DOI: 10.4102/curationis.v23i4.772
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of sexually transmitted diseases among teenagers

Abstract: An ex p lo ra to ry d e sc rip tiv e study was u n d e rtak en , focussing on sexually transmitted diseases (STD) among teenagers. The aim of the study was to explore and describe the possible reasons for the high rate of sexually transmitted diseases in teenagers. The perceptions of teenagers and community nurses regarding sexually transmitted disease among teenagers involved in the teenage clinic in a specific predominantly black area were assessed. Twenty teenagers and five community nurses were participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…Structural barriers to SRH service-seeking highlighted by male adolescents included clinics’ limited operating hours coinciding with school and work hours and an unwelcoming atmosphere for adolescent clients [ 30 33 ]. In one study in Botswana, afternoon and evening hours were recommended by male and female adolescent clients [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Structural barriers to SRH service-seeking highlighted by male adolescents included clinics’ limited operating hours coinciding with school and work hours and an unwelcoming atmosphere for adolescent clients [ 30 33 ]. In one study in Botswana, afternoon and evening hours were recommended by male and female adolescent clients [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…Across studies, health providers’ disregard for privacy [ 19 , 39 44 , 48 ], their expressions of negative judgment of adolescents seeking services [ 19 , 32 , 40 , 41 , 43 , 44 , 48 , 57 , 58 ], and general “lack of respect” for or desire to be approached by youth [ 33 , 66 ] indicate some health care workers in sub-Saharan Africa have attitudes and beliefs impeding their ability to meet the needs of adolescent clients. Furthermore, adolescent patients in a study in Uganda reported feeling rushed by providers during service [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, analyses of abstinence-only curricula have found that, in addition to withholding information from adolescents, they often contain misleading or altogether inaccurate medical information on disease risk and pregnancy rates [9]. Young people are particularly susceptible to myths about sexuality and reproductive health in many different cultural contexts [13,1015]. In a national environment in which the government promotes abstinence from sexual activity until marriage as the only way to prevent pregnancy and transmission of sexually transmitted infections, it is perhaps not very surprising that writers would worry about the pregnancy risk entailed in an act of oral sex, or ask for help in understanding how the “entire sexual thing works,” or be confused about what constitutes protected sex.…”
Section: Discussionmentioning
confidence: 99%
“…23 Two additional articles described qualitative research performed in Africa that discussed the role of training health care workers in AM. Diale and Roos 24 described a qualitative study that found that condescending and negative provider attitudes were a serious barrier to care for adolescents with STIs; they laid out steps for educating community nurses in communication. O'Malley et al 25 explained an innovative study utilizing picture books and cartoons for disclosure of HIV status to HIV-infected children.…”
Section: Scholarly Articles Describing Educational Interventions And/mentioning
confidence: 99%